Effects of Encapsulated Okra (Abelmoschus Esculentus L.) on Intestinal Morphology, Microbiological and Physicochemical Properties of Meat in Broiler Chicken - Harvey Febrianta; Nadia Maharani; Meireni Cahyowati; Dave Mangindaan (International Journal of Science and Environment (IJSE), 2026)
This study investigates the impact of encapsulated okra (Abelmoschus esculentus L.) using an amorphous maltodextrin matrix on microbiological parameters, intestinal morphology, and the physicochemical properties of meat in broiler chickens. The study used 200 broiler chickens of the MB-202 Platinum strain, aged 15 days, with an average body weight of 430 ± 0.31 g. The research material consisted of okra powder encapsulated with an amorphous maltodextrin matrix (CMO). The CMO was mixed into the basal feed under the following treatments: MCF-0, control or basal feed; MCF-1, basal feed + 0.5% CMO; MCF-2, basal feed + 1% CMO; and MCF-3, basal feed + 1.5% CMO. The variables measured included microbiological parameters, lactic acid bacteria and coliforms in the duodenum, jejunum, and ileum, intestinal morphology, and physicochemical properties of meat. Results showed that adding CMO supplementation significantly affected (P<0.05) total LAB, coliform counts in the jejunum and ileum, intestinal pH, villus height and crypt depth in the duodenum, jejunum, and ileum, the villus height to crypt depth ratio in all intestinal segments, and abdominal fat. However, CMO supplementation did not significantly affect water holding capacity, tenderness, color, dressing percentage, or meat moisture content. The study concluded that okra encapsulated with maltodextrin can improve the small intestinal profile and selected physicochemical characteristics of meat, while increasing LAB and reducing coliform populations in broiler chickens.